"Please do not act violently towards the staff": Expressions and causes of anger, violence, and aggression in Israeli cancer patients and their families from the perspective of oncologists. (October 2019) - Granek, Leeat; Ben-David, Merav; Bar-Sela, Gil; Shapira, Shahar; Ariad, Samuel
Expressions of anger within the healthcare context are a common occurrence, particularly in clinical situations where patients can experience emotional distress in the face of illness. The purpose of this study was to examine one aspect of this phenomenon by looking at expressions and causes of anger among Israeli cancer patients and their families from the perspective of oncologists who treat them. Twenty-two Israeli oncologists were interviewed from three oncology centers between March 2013 and June 2014. The grounded theory method was used to collect and analyze the data. Our study revealed that oncologists are exposed to and cope with expressions and acts of anger, aggression, and violence from some of their cancer patients and their families. The causes of this anger include physician blame, unrealistic treatment expectations, perceived errors in communication, and lack of follow up with bereaved families. Our study also revealed that the cultural context affected patient–physician interactions, including anger. This context included a culture that has open interpersonal boundaries and is family-oriented; a multicultural society that includes citizens with different cultural norms and expectations around cancer care; and a strained healthcare system that leaves oncologists limited in time and resources, including limited access to palliative care. Policy implications include reducing oncologist workload by hiring more mental health professionals, having translators available on site to help with language barriers, reducing administrative burdens, and incorporating palliative care widely to help with the psychosocial and physical care of patients and families.